Quality Of District Integrated Administrative Services In District Office Sokaraja Banyumas - Novanis, Ria; Warsono, Hardi (Journal of Public Policy and Management Review, 2019)
Getting of quality public services is the hope of every community. In order to create quality public services, the government passed a law that Permendagri Number 4 of 2010 concerning the Guidelines for District Integrated Administrative Services (PATEN). PATEN aims to improve the quality and bring services closer to the community. This study aims to determine how the quality of PATEN implementation in the Sokaraja District Office in Banyumas, and to know what factors support and hinder the implementation. There are five dimensions used to measure the quality of services provided, these dimensions include tangible, reliability, responsiveness, assurance and empathy. And as to know influencing factors are seen from human resources, strategic, system and customer factors. This study uses descriptive qualitative research methods . The data was collected by interviews with informants, observation, and documentation obtained from actual documents relating to the object of research. The results of this study indicate that the quality of PATENTs in the Sokaraja District Office in Banyumas has not been going well, and it is necessary to hold improvements in the implementation of its services on the dimensions of tangible, reliability and responsiveness. Whereas in the influencing factors, it is known that the strategy factors and customer factors are categorized as inhibiting factors. Improvement of services provided can be in the form of additional infrastructure, disciplinary staff, making Standar Operational Procedure and optimizing the capabilities of staff.